Production of enriched cakes by apple pulp and peel powder and evaluation of chemical, functional and textural properties - Hosseini, Ahmadreza; Pazhouhandeh, Fahimeh (Vitae, 2023)
Background: Apple pomace is a by-product of the fruit juice industry and comprises peel, seed, stem, and pulp tissues. This by-product contains dietary fiber, polyphenols, vitamins, and organic acids that can benefit human health and have a high potential as a dietary source. Baked products are well-known food types to humans and have a key role in feeding people worldwide. Nowadays, enriched products such as bread, cakes, and biscuits are available in stores. Different studies worldwide have been done about applying fruit juice industry by-products in the bakery. Objective: This research aimed to evaluate apple peel (APE) and pulp (APU) powders separately as a partial substitute for wheat flour in cake production. Methods: Apple peels and pulp, separately produced as residual wastes of juicing, were dried for 3 hours in the oven (60°C). The dried pulp and peel were ground and sieved using a 60 µm mesh. In this research, chemical and physic-chemical analyses were performed according to AACC (Approved Methods of the American Association of Cereal Chemists) and standard food analysis methods. Textural characteristic was analyzed by a texture analyzer (Brookfield CT3-10 Kg, US) equipped with an aluminum probe. Results: Different levels of APE and APU powders (10, 20, and 30 %) were used to enrich the cakes. Wheat flour’s ash, fat, water, and oil absorption capacity were lower than APU and APE, whereas the moisture, protein, bulk density, and pH showed a reverse trend. Adding APU and APP to the cake formula increased total dietary fiber (TDF) from 4.14 % in the control sample to 27.71 % in the sample with 30 % apple peel powder (APE-30). The highest a* colorimetric parameter (redness) in the cake core was 3.82 in the APE-30 sample. The addition of APE and APU significantly increased the hardness, gumminess, and chewiness of the samples (p<0.05). APE-10 samples could improve the nutritional properties of the cakes without significant reduction (p>0.05) in overall acceptance compared to the control sample. Conclusion: The results of this research demonstrated that a partial replacement of wheat flour with apple pulp and peel significantly increased the dietary fiber, especially insoluble fiber, compared to the control sample. Apple pulp powder and apple peel powder have the potential for use in cake making as a good source of dietary fiber.